GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA PERANGKAT DESA KECAMATAN SUBAH KAB. BATANG - Fatria Adianto; Rr Hawik Ervina; Rita Meiriyanti (CV. Armas Suan Sejahtera, 2025)
This research examines Village Apparatus in Subah District, Batang Regency. This research aims to determine the influence of leadership style, motivation and work environment on job satisfaction of village officials in Subah District, Kab. Stem. The research method in this research is quantitative descriptive analysis. The population in this research is 17 villages in the Subah sub-district with a total of 204 village officials, while the sample in this research is 204 village officials. Determining the sample size used the saturated sampling technique method. Data analysis in this study used the SPSS Version 26 program. The analysis technique used multiple linear regression. The results of this research are that the leadership style variable has a positive and significant effect on job satisfaction, the motivation variable has a positive and significant effect on job satisfaction and the work environment has a positive effect on job satisfaction